Numerical Modelling of Wind Flow In Street Canyon Between High-Rise Buildings with Angle of Attack Modifications - Doni Priambodo; Yongky Sanjaya; Prasanti Widyasih Sarli; Herlien Dwiarti Setio (Media Komunikasi Teknik Sipil, 2023)
In fluid dynamics analysis, one of the things to do is to perform numerical modeling validated on the results of experimentation. In numerical modeling of wind flow there are several forms of modeling used including RANS, LES, DNS, etc. where the modeling has its own advantages and disadvantages. Among these models, RANS is a model that has the cheapest computer expense compared to other models so that it has the highest workability. Therefore, rans method testing (Reynolds Averaged Navier Stokes) was conducted to determine the capability of turbulence models in checking wind speed contours on the road between 4 simple symmetrical tall buildings with 0o, 30o, and 45o attack an gles validated with the results of experimentation. This research was conducted using RANS modeling (Reynolds Averaged Navier Stokes) and standard turbulence model k-ε and validated using Low Speed Wind Tunnel and PIV (Particle Image Velocimetry). According to the results of the test, U/Uo wind speed conditions obtained in wind modeling with RANS and k-ε standards have errors that are still acceptable.